Factores en el Desarrollo de estrategias de afrontamiento y capacidad de resiliencia en mujeres diagnosticadas con cáncer en la fase inicial (2023)
In Colombia, a large number of women are exposed to the unexpected diagnosis of cancer, directly affecting their mental, physical and emotional health, discovering psychosomatic effects reflected in behaviors such as: depression, suicide attempts, denial, guilt, social isolation.